Whole plant acclimation responses by finger millet to low nitrogen stress - Goron, Travis L.; Bhosekar, Vijay K.; Shearer, Charles R.; Watts, Sophia; Raizada, Manish N. (Frontiers in Plant Science, 2015)
The small grain cereal, finger millet (FM, Eleusine coracana L. Gaertn), is valued by subsistence farmers in India and East Africa as a low-input crop. It is reported by farmers to require no added nitrogen, or only residual N, to produce grain. Exact mechanisms underlying the acclimation responses of FM to low N are largely unknown, both above and below ground. In particular, the responses of FM roots and root hairs to N or any other nutrient have not previously been reported. Given its low N requirement, FM also provides a rare opportunity to study long-term responses to N starvation in a cereal. The objective of this study was to survey the shoot and root morphometric responses of FM, including root hairs, to low N stress. Plants were grown in pails in a semi-hydroponic system on clay containing extremely low background N, supplemented with N or no N. To our surprise, plants grown without deliberately added N grew to maturity, looked relatively normal and produced healthy seed heads. Plants responded to the low N treatment by decreasing shoot, root and seed head biomass. These declines under low N were associated with decreased shoot tiller number, crown root number, total crown root length and total lateral root length, but with no consistent changes in root hair traits. Changes in tiller and crown root number appeared to coordinate the above and below ground acclimation responses to N. We discuss the remarkable ability of FM to grow to maturity without deliberately added N. The results suggest that FM should be further explored to understand this trait. Our observations are consistent with indigenous knowledge from subsistence farmers in Africa and Asia that this crop can survive extreme environments.